PROGRAM SEKOLAH DASAR BERSIH DAN SEHAT DI SD NEGERI 43 PEKANBARU - Susi Susanti; Isjoni Isjoni; Daeng Ayub Natuna (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2019)
This study is a qualitative research that aims to determine how the implementation of the program an SD Clean Healthy (SDBS) in SD Negeri 43 Pekanbaru. This study focuses on the implementation of the program of Clean and Healthy SD (SDBS) in SD Negeri 43 Pekanbaru. Subfokus this study consisted of 1) How is the implementation of the primary school program a clean and healthy in SD Negeri 43 Pekanbaru, 2) How to efforts to implement school programs are clean and healthy at the SD Negeri 43 Pekanbaru, 3) How will the results of the program the school is clean and healthy (SDBS) SD Negeri 43 Pekanbaru. This research data collection through interviews, observation and documentation. The results showed that the subfokus beginning of primary school program a clean and healthy (SDBS) in SD Negeri 43 Pekanbaru already in the good category, subfokus efforts to implement primary school program a clean and healthy (SDBS) in SD Negeri 43 Pekanbaru already performing well, in exercising their success subfokus program clean and healthy primary school (SDBS) in SD Negeri 43 Pekanbaru also been performing well. It can be seen that for implementation of a Clean and Healthy Primary School (SDBS) students at SDN 43 Pekanbaru overall and subfokus aspects of research can be said is good because of the three subfokus everything is located in both categories.